2007
DOI: 10.1007/s11262-007-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Marek’s disease virus unique genes pp38 and pp24 are essential for transactivating the bi-directional promoters for the 1.8 kb mRNA transcripts

Abstract: The pp38 and pp24 genes of Marek's diseases virus (MDV) share the same promoter, which controls the transcription of pp38 or pp24 and a 1.8-kb mRNA bi-directionally. To understand the trans-activating activity of pp38 and pp24 on the bi-directional promoter, both genes were cloned into pcDNA-3 or pBudCE4.1 vectors either singly or in combination. These plasmids were expressed in transfected chicken embryonic fibroblast (CEF) cells. Chloramphenicol acetyltransferase (CAT) activity expressed under the control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Recently, we carried out a transfection with the plasmid pP(1.8 kb)-CAT to qualitatively analyze the enhancement of pp38 to its upstream bi-directional promoter, and the result showed pp38 could significantly enhance the activity of the promoter, which, however, depended on the cooperation of pp24 [12] . In this work, we used EGFP as a reporter, and the transfected results further verified the importance of pp24 to pp38 in the enhancement to the bi-directional promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we carried out a transfection with the plasmid pP(1.8 kb)-CAT to qualitatively analyze the enhancement of pp38 to its upstream bi-directional promoter, and the result showed pp38 could significantly enhance the activity of the promoter, which, however, depended on the cooperation of pp24 [12] . In this work, we used EGFP as a reporter, and the transfected results further verified the importance of pp24 to pp38 in the enhancement to the bi-directional promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chloramphenicol acetyltransferase (CAT) gene was used as a reporter to verify that the enhancement of pp38 to the promoter depends on the existence of pp24 [12] . In this work, we used enhanced green fluorescence protein (EGFP) gene as a reporter to confirm that the co-existence of pp38 and pp24 is essential to activity of the bi-directional promoter.…”
mentioning
confidence: 99%
“…Marek's disease virus (MDV) is a highly transmissible cell-associated neuropathic oncogenic alphaherpes virus (Lee et al, 2000;Tulman et al, 2000) affecting poultry health worldwide, characterized by T-cell lymphomas in peripheral nerves and visceral organs (Ding et al, 2007) resulting in considerable economic losses.Three serotypes of MDV have been classified; MDV-1 which is the pathogenic one for chickens, causing marek's disease (MD), is classified as gallid herpes virus II. The second serotype; MDV-2, is gallid herpes virus III and the third and last one is a MDV-3 (as HVT) as meleagrid herpes virus.…”
Section: Introductionmentioning
confidence: 99%
“…They were located on I RL region and separated by a short sequence of only about 305 bp but with several enhancer motifs such as TATA-box, CAAT-box, Oct-1, and Sp1, and as a bi-directional promoter to initiate transcription of two genes in opposite directions [7], [8], [9]. By use of GFP gene and chloramphenicol acetyltransferase ( CAT ) as reporter genes, it was demonstrated that the activity of the bi-directional promoter could be strongly increased by the expression of MDV pp38/pp24 dimers as a trans-acting transcriptional factor [10]. However, it is still unclear whether this bi-directional promoter is able to simultaneously drive two genes expression in both directions.…”
Section: Introductionmentioning
confidence: 99%